Anion‐Exchange Formation of Hollow NiCo2S4 Nanoboxes from Mesocrystalline Nickel Cobalt Carbonate Nanocubes towards Enhanced Pseudocapacitive Properties. Issue 6 (23rd May 2016) - Hou, Linrui; Hua, Hui; Bao, Ruiqi; Chen, Zhiyi; Yang, Chao; Zhu, Siqi; Pang, Gang; Tong, Liuniu; Yuan, Changzhou; Zhang, Xiaogang
Abstract: An efficient anion‐exchange protocol was investigated for the controllable fabrication of hollow NiCo2 S4 nanoboxes (NBs) from mesocrystalline nickel cobalt carbonate nanocubes as promising pseudocapacitive materials for electrochemical capacitors. The underlying processes of the formation of the hollow architecture were systematically investigated. Originating from the unique structural and compositional advantages, the resultant hollow NiCo2 S4 NB electrode with a loading of 5 mg cm 2 delivered a large specific capacitance of 777 F g −1 at a high rate of 4 A g −1 in a three‐electrode configuration with 6 m KOH as electrolyte. Furthermore, an asymmetric device constructed with the hollow NBs and activated carbon (AC) as positive and negative electrodes, respectively, showed extraordinary supercapacitance within an electrochemically operating voltage window from 0.0 to 1.5 V. The unique AC//NiCo2 S4 NB hybrid capacitor exhibited a large specific energy density (active mass normalized) of approximately 17.1 W h kg −1 at a high power density of 2250 W kg −1, and desirable cycling durability with approximately 75 % specific capacitance retention after 5000 consecutive cycles at a current rate of 2 A g −1 . These electrochemical investigations strongly indicated that the as‐fabricated hollow NiCo2 S4 NBs can be elegantly utilized as powerful candidates for advanced electrode platforms. Abstract : Boxing clever : Hollow NiCo2 S4 nanoboxes were controllably fabricated from mesocrystalline metal carbonate nanocubes by an efficient anion‐exchange protocol, and demonstrated supercapacitance with a large energy density and desirable cycling performance at high rates (see figure).